A functional‐trait approach reveals community diversity and assembly processes responses to flood disturbance in a subtropical wetland. Issue 1 (29th October 2014) - Fu, Hui; Zhong, Jiayou; Yuan, Guixiang; Guo, Chunjing; Ding, Huijun; Feng, Qian; Fu, Qun
Abstract: Despite the strong effects of disturbance on plant community diversity and assembly, we do not fully understand how different aspects of taxonomic or functional diversity respond to disturbance or how different assembly processes change along a disturbance gradient. In this study, plant communities were sampled and the distributions of three functional traits were measured in 45 plots across a flood disturbance gradient in Poyang Lake wetland in China. We examined the within‐community means, ranges, variances, kurtoses, and other parameters of trait values. Results showed that the effects of disturbance depended largely on the aspects of diversity considered. Along the flood disturbance gradient, taxonomic/functional richness did not change, while Shannon–Wiener diversity and evenness and functional evenness and dispersion showed significant unimodal patterns. Communities experiencing the highest disturbance levels tended to have significantly shorter shoot heights with lower specific leaf area (SLA). We also found a significant non‐random functional trait distribution: a significant reduction in the range and variance of SLA and a more even distribution of the measured traits compared with the null model. Our results highlight that niche‐based assembly processes play structuring roles in wetland plant community response to flood disturbance gradients and that both environmental filtering and limiting similarity can work on the same traits (e.g., SLA) through hierarchical effects on the distribution of functional traits within communities.